2019
DOI: 10.1177/1071100719866700
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experience With Polyvinyl Alcohol Hydrogel Implant for Pathology of the Second Metatarsal Head

Abstract: Background: There is no consensus regarding which surgical technique is most beneficial for pathology of the second metatarsophalangeal joint. We report the use of polyvinyl alcohol hydrogel synthetic cartilage implant hemiarthroplasty for pathology of the second metatarsal head that has failed nonoperative treatment and present 5 cases with a minimum 15 months of follow-up. Methods: The technique for synthetic cartilage hemiarthroplasty of the second metatarsal head is described. The postoperative protocol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…Demographically, our cohort treated with PVA implant for lesser toe pathologies is consistent with the existing literature with regard to age, sex, and clinical follow-up times. 3,9 Our cohort was 100% female, and 5 of 13 patients presented with Freiberg’s disease, which is consistent with the current literature suggesting the prevalence of Freiberg’s disease predominantly in females. 4,5…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Demographically, our cohort treated with PVA implant for lesser toe pathologies is consistent with the existing literature with regard to age, sex, and clinical follow-up times. 3,9 Our cohort was 100% female, and 5 of 13 patients presented with Freiberg’s disease, which is consistent with the current literature suggesting the prevalence of Freiberg’s disease predominantly in females. 4,5…”
Section: Discussionsupporting
confidence: 91%
“…6 Previous study has also shown that 80%, 60%, and 50% of second, third, and fourth MT heads, respectively, could accommodate the 8-mm implant. In a recent study by Glazebrook and colleagues, 9 the authors presented a case series of 5 patients who underwent PVA implantation for Freiberg's infraction or arthritis of the second MT head and reported good clinical outcomes and no complications at an average of 25 months of follow-up. The authors utilized the 8-mm implant in all patients.…”
Section: Sizing Of the Implant Remains An Important Considerationmentioning
confidence: 99%
“…Prosthesis failure occurred in 1 patient. Glazebrook et al 47 presented their preliminary experience with Cartiva (Carticept Medical, Alpharetta, GA, USA), a polyvinyl alcohol hydrogel implant for pathology of the second metatarsal head. The results demonstrated good outcomes and no complications in 5 patients (mean age, 57 years) at a mean follow-up of 25 months.…”
Section: Implant Arthroplastymentioning
confidence: 99%
“…Glazebrook et al 5 reported on 5 cases of polyvinyl alcohol (PVA) hydrogel synthetic cartilage implant hemiarthroplasty of the second metatarsal head using an 8-mm implant. No complications were found, patients reported little to no pain, and good range of motion was noted at a mean of 25 months of follow-up.…”
Section: Forefootmentioning
confidence: 99%